Between power and duty: Advertising and its role in the formation of gender stereotypes. First notes - Mendoza Cuéllar, Héctor (2012)
The present paper is an approach to the construction, development and dissemination of gender roles (male and female) from the publicity established in Lima. This self-critical look at the advertising profession rather than blame wishes to describe a reality often ignored or filtered by various factors. It also proposes ways to deal with this problem facing its principal actors: Advertising, customers and especially teachers and students from different universities and institutes that apparently do not regard this as an important part of the training provided to new generations favoring perpetuation of stereotypical gender roles. For this article we have resorted to bibliographic research, analysis of advertisements and interviews with professionals who can provide different and complementary perspectives in order to understand this reality, seek consensus and pathways to a new approach in advertising and gender.